2014
DOI: 10.1007/s12664-014-0488-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, anthropometric, biochemical, and histological characteristics of nonobese nonalcoholic fatty liver disease patients of Bangladesh

Abstract: Nonobese was 25.6 % among NAFLD patients of Bangladesh, and 53.1 % of nonobese NAFLD cases were NASH. Though they were nonobese by BMI grade, they were metabolically similar to obese. Males were predominant in the nonobese, whereas females in the obese. NASH and fibrosis were similar in the obese and nonobese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
92
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 39 publications
16
92
1
Order By: Relevance
“…[15]. This also agree with Alam et al, 2014 who found NASH in 53% of lean weighted patients with NAFLD [16]. Our study shows that the mean HOMA IR value in non-obese patients wasn't significantly lower than that in obese patients.…”
Section: Discussionsupporting
confidence: 92%
“…[15]. This also agree with Alam et al, 2014 who found NASH in 53% of lean weighted patients with NAFLD [16]. Our study shows that the mean HOMA IR value in non-obese patients wasn't significantly lower than that in obese patients.…”
Section: Discussionsupporting
confidence: 92%
“…Males were predominant in the non-obese, whereas females in the obese. NASH and fibrosis were similar in the obese and non-obese [45]. The prevalence of NASH is high.…”
Section: Current Research Work's Findings On Nafld In Bangladesh-naflmentioning
confidence: 73%
“…It does not mean that only obese people are at risk of NAFLD, study showed that, among NAFLD patients of Bangladesh 25.6% was non-obese, and 53.1 % of nonobese NAFLD cases had nonalcoholic steatohepatitis (NASH) [45]. Though they were not obese by BMI grade, they were metabolically similar to obese.…”
Section: Current Research Work's Findings On Nafld In Bangladesh-naflmentioning
confidence: 99%
See 1 more Smart Citation
“…Male are largely dominating in nonobese group, where female are in obese group [36]. High BMI, central obesity, triglyceridemia and age are important risk factors for Bangladeshi people, and risk factors contributed about 29% risk for the occurrence of NASH [37].…”
Section: Depiction Of the Magnitude Among Different Risk Groupmentioning
confidence: 99%